(untitled) (The Peerian Journal, 2026)
The article examines international models of financial support for preschool education and analyzes the possibilities of their adaptation in the context of Uzbekistan, with special attention to the Republic of Karakalpakstan. Using a comparative institutional approach, the study identifies social-oriented, mixed, and liberal financing models and evaluates their advantages and limitations. The results demonstrate that hybrid models based on public–private partnership mechanisms provide the most balanced solution in terms of social accessibility, fiscal sustainability, and institutional efficiency. The findings form a conceptual basis for improving preschool education financing systems in transition economies